2019
DOI: 10.3390/en12040593
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Causes of Power-Converter Failure in Wind Turbines based on Comprehensive Field-Data and Damage Analysis

Abstract: Power converters are among the most frequently failing components of wind turbines. Despite their massive economic impact, the actual causes and mechanisms underlying these failures have remained in the dark for many years. In view of this situation, a large consortium of three research institutes and 16 companies, including wind-turbine and component manufacturers, operators and maintenance-service providers has joined forces to identify the main causes and driving factors of the power-converter failures in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…The failure and repair rates associated with the composed components of the studied SSG converter can be obtained from the manufacturer information. However, due to the lack of reliable data, the failure and repair rates of different components can be determined as presented in [17][18][19][20]. Based on the reliability data obtained for different components, in this paper, the equivalent failure and repair rates of the SSG converter are considered to be 2 and 98 times per year, respectively.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The failure and repair rates associated with the composed components of the studied SSG converter can be obtained from the manufacturer information. However, due to the lack of reliable data, the failure and repair rates of different components can be determined as presented in [17][18][19][20]. Based on the reliability data obtained for different components, in this paper, the equivalent failure and repair rates of the SSG converter are considered to be 2 and 98 times per year, respectively.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…A fault in any component of a power conversion chain can result in a partial or total loss of system control and an unplanned maintenance leading to significant production losses. In other situations, these faults can lead to disastrous consequences and risks for personnel, facilities, and the environment, especially when the systems are integrated into safety-relevant facilities such as transport, health, power grids, robotics, or nuclear power plants [7].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have identified converters as one of the most frequently failing subsystem in WTs [3,4]. Among converter components, phase modules (insulated gate bipolar transistors (IGBTs), gate-drive circuits, capacitors) were found to be more critical in terms of failure frequency [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal cycling is not the only failure mechanism in IGBT modules. Fischer et al [5] identified ambient humidity and moisture as the dominant failure mechanism in WT converters. However, in their study majority of the converters were liquid-cooled.…”
Section: Introductionmentioning
confidence: 99%